Fabrication and characterisation of mixed oxide-covered mesh electrodes of nominal composition Ni(x)Co(1 − x)Oy supported on stainless-steel prepared by thermal decomposition using the slow cooling rate method. (10th March 2016) - Ribeiro, Fernando M.; Faria, Emanuel R.; Verly, Rodrigo M.; Franco, Débora V.; Da Silva, Leonardo M.
Graphical abstract: Highlights: Mixed oxide-covered mesh electrodes containing nickel and cobalt (Ni( x )Co(1 − x )O y ) prepared by thermal decomposition using the slow cooling rate method were supported on a stainless-steel fine-mesh support aiming for environmental applications in SPE filter-press cells. The overpotential for the oxygen evolution reaction (OER) obtained in electrolyte-free water strongly depends on the oxide composition (Co and Ni contents). The stability tests carried out during electrolysis of the electrolyte-free water using an SPE filter-press cell revealed that the Ni( x )Co(1 − x )O y mixed oxide electrodes are more stable in acidic conditions than pure oxides (e.g., NiO and Co3 O4 ). Abstract: Mixed oxide-covered mesh electrodes (MOME) containing Co and Ni of nominal composition MOME-Ni( x )Co(1 − x )O y were prepared by thermal decomposition on a stainless-steel fine-mesh support using the slow cooling rate method in order to obtain fluid-permeable electrodes (FPE) for environmental applications in solid polymer electrolyte (SPE) cells. The surface morphology and true composition of the oxide layers were investigated using SEM and EDS techniques, respectively. The electrochemical characterisation study was carried out in electrolyte-free water using a filter-press cell in the zero-gap configuration with Nafion ® 117 membrane as the SPE. SEM images revealed that the mixed oxide coatings exhibited a compact surface morphology. A very good adhesion of the oxide layers to the stainless-steel fine-mesh support was achieved after the polishing of the latter using emery paper. EDS data revealed that the Co:Ni ratios were in agreement with the nominal compositions obtained from the precursor salt solutions. The cyclic voltammetry study revealed that a reversible pseudo-capacitive behaviour can be attributed to the solid-state surface redox transitions occurring at the three-phase interfacial regions in an acidic environment. Polarisation curves obtained for the oxygen evolution reaction (OER) in electrolyte-free water revealed the overpotential is strongly affected by the Co percentage, the highest overpotentials being observed for the electrodes containing 0, 10 and 70 mol% Co. The stability tests carried out in electrolyte-free water during the OER ( j = 400 mA cm −2 and T = 24 °C) revealed that the Ni( x )Co(1 − x )O y mixed oxide electrodes are more stable than the pure oxides (e.g., NiO and Co3 O4 ). The use of an SPE resulted in good stabilisation of the Co + Ni mixed oxide electrodes during electrolysis of the electrolyte-free water.